Pengembangan Perangkat Pembelajaran IPA Dengan Model Kooperatif Tipe Jigsaw Untuk Meningkatkan Pemahaman Konsep Materi Kerusakan Lingkungan Alam Pada Siswa KelaS V SD Negeri 2 Labuan - Abdurahman Rifai; Sarjan N. Husain; I Nengah Kundera (Universitas Tadulako, 2015)
The research was conducted in the second semester the SDN Negeri.2 Labuan school year 2013/2014. Problems in research is (1) whether there is a revision component in the development of lesson plan, teacher reference books, through 4D models in the discussion of damage to the natural environment learning model jigsaw The Elementary School fifth grade students Labuan?; (2) What factors are revised in the development of lesson plans, teacher reference books, by using 4D procedure in the discussion of damage to the natural environment through the model jigsaw in Elementary School fifth grade students Labuan?: This research purposes determine the components in the learning device gets priority for repair or revised so understanding the concept of matter damage to the natural environment in the fifth grade students of SD Negeri 2 Labuan can be increased. This type of research is the development of research, concluded that the lesson plan well designed and using the right approach will be very effective in improving outcomes and learning activities of students.